An Oscar Wilde Chronology
X, 105 p.
Keywords: Providing details of Wilde's life and work in an easily accessible profile, this biography makes use of surviving letters, notebooks, diaries and documents, as well as other researched biographies. Other author's in the series include Pope, Byron, Dickens, Kipling, and Tennyson.